2010
DOI: 10.1007/s10562-010-0382-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Support Acidity on Olefin Metathesis over Heterogeneous Mo/HBeta Catalyst: A DFT Study

Abstract: The effect of support acidity on the crossmetathesis of ethylene and 2-butylene to propylene over heterogeneous Mo/HBeta catalyst was studied by density functional theory (DFT) calculations. The zeolite acidity was mimicked by changing the terminating Si-H bond lengths. Both of the initiating formation and propagating processes of Mo-carbene were investigated. It is found that there is a correlation between the zeolite acidity and the activation barrier. The influence of acidity on the initial Mo-carbene forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…A detailed DFT study on the crossmetathesis of ethene and 2-butene to propene using the above models demonstrated that the acidity of the support would affect the transition-state structures as well as the activation barriers. 133 The DFT calculations revealed that olefin metathesis would occur more easily over more acidic heterogeneous catalysts, which is consistent with the experimental results from our group and others. 129,[134][135][136] However, too much Brønsted acidity may also cause side reactions such as olefin isomerization and oligomerization.…”
Section: 121supporting
confidence: 90%
See 1 more Smart Citation
“…A detailed DFT study on the crossmetathesis of ethene and 2-butene to propene using the above models demonstrated that the acidity of the support would affect the transition-state structures as well as the activation barriers. 133 The DFT calculations revealed that olefin metathesis would occur more easily over more acidic heterogeneous catalysts, which is consistent with the experimental results from our group and others. 129,[134][135][136] However, too much Brønsted acidity may also cause side reactions such as olefin isomerization and oligomerization.…”
Section: 121supporting
confidence: 90%
“…129 In order to give a comprehensive understanding of the mechanism, DFT calculations were performed on the Mo/HBeta catalyst with different acidities. 133 The Si-H distance of the cluster model was set between 1.30 and 2.25 Å to represent the supports with different Brønsted acid strengths. 77 Fig .…”
Section: 121mentioning
confidence: 99%
“…A previous experimental study of COE-4 zeolites confirmed the Si(OH) 2 groups were attached to the bridging unit at the linker position by using solid-state 29 Si and 1 H MAS NMR measurements. [14] Tetravalent Si(OH) 2 could be substituted by the triva-lent T atom at the linker position to result in the Brønsted acidity of the T-COE-4 zeolites.…”
Section: Substitution Energy Of Interlayer-expanded T-coe-4mentioning
confidence: 74%
“…Kang et al [28] carried out periodic DFT to study the methanol adsorption in isomorphously substituted M-AlPO-34 (M = Mn, Zn, Mg, Si, Ti, and Zr) zeolites. [29,30] Moreover, acidity characterization may also be achieved by the adsorption of suitable basic probe molecules, such as ammonia, pyridine or trimethylphosphine. [28] From DFT calculations, we revealed the pentavalent Mo-carbene to be the active species in olefin metathesis on Mo/HBeta zeolite, and the greater the acidity was, the higher the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation